KECERDASAN MAJEMUK PESERTA DIDIK KELAS X-B SMAN 6 BONE BERDASARKAN TEORI GARDNER - Miftahul Khairah; Syinta M; Rani Awaliah Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the dominant types of Multiple Intelligences in class X-B students of SMAN 6 Bone based on Howard Gardner's theory. Using a non-statistical quantitative descriptive approach, data were collected through a Google Form-based questionnaire with a Likert scale of 1–3 and analyzed by calculating the scores and percentages of each type of intelligence. The study subjects were 30 students. The results showed that interpersonal intelligence was the most dominant type, followed by intrapersonal and verbal-linguistic intelligence. These findings reflect the condition of adolescent social development and demonstrate the importance of a collaborative learning approach. This study provides recommendations for teachers and counselors to design educational strategies that are appropriate to students' dominant potential and support their future career planning.